Impact of electrical energy efficiency programs, case study: food processing companies in cuenca, ecuador (2014)
This exploratory study illustrates the effects of the application of electrical energy efficiency programs in 7 food processing companies in Cuenca, Ecuador. The research encompassed phases of diagnosis, intervention and evaluation. A comparative analysis between the companies was conducted: energy consumption versus product volume, energy-quality analysis, relation between compliance/specific energy consumption, and the impact on CO2 emissions. Results revealed that the acceptance to the recommendations of savings is biased by the level of investments and the willing/proneness of the administration. The study showed that interventions had a partial effect on the reduction of the specific energy consumption in 4 companies. In addition, it has obtained a positive effect on the power factor correction in one company and an improvement on the load balance in 5. The research showed the existence of a significant reduction of emissions post-intervention, highlighting the effectiveness of the programs.